Genetic and functional characterisation of the P/Q calcium channel in episodic ataxia with epilepsy - Rajakulendran, Sanjeev (Blackwell Science Inc, 2010)
Mutations in CACNA1A, which encodes the principal subunit of the P/Q calcium channel, underlie episodic ataxia type 2 (EA2). In addition, some patients with episodic ataxia complicated by epilepsy have been shown to harbour CACNA1A mutations, raising the possibility that P/Q channel dysfunction may be linked to human epilepsy. We undertook a review of all published CACNA1A EA2 cases and this showed that 7% have epilepsy – representing a sevenfold increased epilepsy risk compared to the background population risk (P < 0.001). We also studied a series of 17 individuals with episodic ataxia accompanied by epilepsy and/or clearly epileptiform electroencephalograms (EEGs). We screened the entire coding region of CACNA1A for point mutations and rearrangements to determine if genetic variation in the gene is associated with the epilepsy phenotype, and measured the functional impact of all missense variations on heterologously expressed P/Q channels. We identified two large scale deletions and two new missense mutations in CACNA1A. When expressed, L621R had little detectable effect on P/Q channel function, while the other missense change, G540R, caused an approximately 30% reduction in current density. In nine patients we also identified the previously reported non-synonymous coding variants (E921D and E993V) which also resulted in impairment of P/Q channel function. Taken together, 12 of the 17 patients have genetic changes which decrease P/Q channel function. We conclude that variants in the coding region of CACNA1A that confer a loss of P/Q-type channel function are associated with episodic ataxia and epilepsy. Our data suggest that functional stratification of all variants, including common polymorphisms, rare variants and novel mutations, may provide new insights into the mechanisms of channelopathies.